Multisite Culinary Medicine Curriculum Is Associated With Cardioprotective Dietary Patterns and Lifestyle Medicine Competencies Among Medical Trainees. Issue 2 (March 2020) - Razavi, Alexander C.; Monlezun, Dominique J.; Sapin, Alexander; Stauber, Zachary; Schradle, Kara; Schlag, Emily; Dyer, Amber; Gagen, Brennan; McCormack, Isabella G.; Akhiwu, Ofure; Ross, Alexandria; McWhorter, John Wesley; et al.
Background. Adherence to Mediterranean dietary patterns reduces the incidence of cardiovascular disease and other major chronic diseases. We aimed to assess the association between participation in kitchen-based nutrition education and Mediterranean diet intake and lifestyle medicine counseling competencies among medical trainees. Methods. The Cooking for Health Optimization with Patients (CHOP) curriculum is a hands-on cooking-based nutrition education program implemented at 32 medical programs (4125 medical trainees) across the United States. Mediterranean diet intake, nutrition attitudes, and lifestyle medicine counseling competencies were assessed via validated surveys. Multivariable-adjusted logistic regression assessed the relationship of CHOP education with Mediterranean diet intake, nutrition attitudes, and lifestyle medicine counseling competencies. Results. Individuals participating in the CHOP program were 82% more likely to follow the Mediterranean diet compared with those receiving traditional nutrition education (OR = 1.82; P < .001). CHOP participants were more likely to satisfy daily intake of fruits (OR = 1.33; P = .019) and vegetables (OR = 2.06; P < .001) and agree that nutrition counseling should be a routine component of clinical care (OR = 2.43; P < .001). Kitchen-based nutrition education versus traditional curricula is associated with a higher likelihood of total counseling competency involving 25 lifestyle medicine categories (OR = 1.67; P < .001). Conclusion. Kitchen-based nutrition education is associated with cardioprotective dietary patterns and lifestyle medicine counseling among medical trainees.